Human occupations during the Middle Holocene and beginning of the Late Holocene in the Pocitos basin, Puna of Salta, Argentina: New research and regional comparison - Lopez, Gabriel Eduardo Jose (2013)
This article analyzes the human occupations of the Middle Holocene and beginnings of the Late Holocene at Pocitos as compared with other areas of the Salta Puna (Highlands region) such as Pastos Grandes and more generally in a macroregional framework (south-central Andes). Pocitos is a basin presenting an arid environment of salt flat, and with very scant primary productivity. Its location in the Salta Puna, midway between the Puna of Jujuy and that of Catamarca, is suitable for social interaction and cultural communication. From information on surface and stratified contexts from the Middle Holocene and beginnings of the Late Holocene the technological and faunal variability in the area is analyzed. The site serving as a chronological referential base is Abrigo Pozo Cavado.